The Relationship of Social Leadership with Social Capital towards Community Empowerment in Indonesia - Rozikin, Mochammad; Nalikan, Mohammad; ., Sumartono; ., Suryadi; Riyadi, Bambang Slamet (International Journal of Membrane Science and Technology, 2023)
This research aims to predict and analyze the effects of social leadership and social capital on community empowerment. This research adopted a quantitative method. Data were collected through related documentation and survey questionnaires on 100 village leaders in Indonesia across Sumatera, Java, Kalimantan, Sulawesi, Bali, Nusa Tenggara, and Papua. Data were analyzed statistically using Partial Least Square (PLS). The research results were as follows: social leadership positively affected community empowerment; social capital positively affected community empowerment; social leadership positively affected social capital; and social capital fully mediated the relationship between social leadership on community empowerment.